2002
DOI: 10.1071/mf01158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a network of no-take reserves in increasing catch per unit effort and stocks of exploited reef fish at Nabq, South Sinai, Egypt

Abstract: In 1995, in collaboration with local Bedouin fishermen, five no-take fisheries reserves were established within the Nabq Natural Resource Protected Area, South Sinai, Egyptian Red Sea. The abundance, size structure and catch of commercially targeted groupers (Serranidae), emperors (Lethrinidae) and snappers (Lutjanidae) were investigated before the establishment of these reserves, then in 1997 and again in 2000. By 1997, these fish had shown a significant increase in mean abundance within two of the no-take re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Some benefits from the protection were detected within the PA. Since 1995, fishery has been regulated, and after five years of protection the abundance of the main target fish families was found to be significantly greater (Galal, 1999;Galal et al, 2002). However, Galal et al (2002) reported that fishing by Bedouins in Nabq PA had led to a significant decrease in the abundance and mean length of some serranids and lethrinids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some benefits from the protection were detected within the PA. Since 1995, fishery has been regulated, and after five years of protection the abundance of the main target fish families was found to be significantly greater (Galal, 1999;Galal et al, 2002). However, Galal et al (2002) reported that fishing by Bedouins in Nabq PA had led to a significant decrease in the abundance and mean length of some serranids and lethrinids.…”
Section: Resultsmentioning
confidence: 99%
“…Since 1995, fishery has been regulated, and after five years of protection the abundance of the main target fish families was found to be significantly greater (Galal, 1999;Galal et al, 2002). However, Galal et al (2002) reported that fishing by Bedouins in Nabq PA had led to a significant decrease in the abundance and mean length of some serranids and lethrinids. Moreover, the high diversity of the area gives it tourism potential with an average of 18,000 visitors/year (Mabrouk, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In South Sinai (the Egyptian GoA), parrotfish communities are subject to markedly different levels of fishing pressure, ranging from virtually none in Ras Mohammed and Sharm El-Sheikh; increased in Nabq, Dahab, and Abu Galum; and reaching extremely high levels in Nuweiba and Taba. Several previous studies in South Sinai MPAs (Galal et al, 2002(Galal et al, , 2012Ashworth, 2004;Tilot et al, 2008) used UVC to assess the impact of fishing on coral reef fishes (including parrotfishes). However, the majority of these studies were limited to focusing on a specific geographic area or conducted only on one reef habitat.…”
Section: Discussionmentioning
confidence: 99%
“…In Ras Mohammed and Sharm El-Sheikh, all forms of nearshore fishing are prohibited (Pearson and Shehata, 1998;Mabrouk, 2015). Whereas in Nabq and Abu Galum, only local Bedouin fishermen are allowed to fish using traditional fishing methods (Galal et al, 2002). In Dahab, fishing is prohibited at all dive sites (Hasler and Ott, 2008).…”
mentioning
confidence: 99%
“…In Ras Mohammed and Sharm el-Sheikh (south GoA), all forms of nearshore fishing activities are prohibited (Mabrouk, 2015). However, in Nabq (north of Sharm el-Sheikh), fishing is permitted for local Bedouin using their traditional gears (e.g., gillnets and trammel nets) that principally target herbivorous fish species entering the reef flat with the rising tides to feed on algae (Galal et al, 2002). Whereas, in Abu Galum and Dahab (central GoA), fishing is allowed in certain locations and prohibited at dive sites (Hasler and Ott, 2008).…”
Section: Introductionmentioning
confidence: 99%